Quantifying canopy complexity and effects on productivity and resilience in late‐successional hemlock–hardwood forests. Issue 3 (1st April 2015) - Fahey, Robert T.; Fotis, Alexander T.; Woods, Kerry D.
Abstract : The regrowing forests of eastern North America have been an important global C sink over the past 100+ years, but many are now transitioning into late succession. The consequences of this transition are unclear due to uncertainty around the C dynamics of old‐growth forests. Canopy structural complexity (CSC) has been shown to be an important source of variability in C dynamics in younger forests (e.g., in productivity and resilience to disturbance), but its role in late‐successional forests has not been widely addressed. We investigated patterns of CSC in two old‐growth forest landscapes in the Upper Peninsula of Michigan, USA, to assess factors associated with CSC and its influence on productivity and disturbance resilience (to moderate‐severity windstorm). CSC was quantified using a portable below‐canopy LiDAR (PCL) system in 65 plots that also had long‐term (50–70+ years) inventory data, which were used to quantify aboveground net primary productivity (ANPP), disturbance history, and stand characteristics. We found high and variable CSC relative to younger forests across a suite of PCL‐derived metrics. Variation in CSC was driven by species composition and size structure, rather than disturbance history or site characteristics. Recent moderate severity wind disturbance decreased plot‐scale CSC, but increased stand‐scale variation in CSC. The strong positive correlation between CSC and productivity illustrated in younger forests was not present in undisturbed portions of these late‐successional ecosystems. Moderate severity disturbance appeared to reestablish the positive link between CSC and productivity, but this relationship was scale and severity dependent. A positive CSC–productivity relationship was evident at the plot scale with low‐severity, dispersed disturbance, but only at a patch scale in more severely disturbed areas. CSC does not appear to strongly correlate with variation in productivity in undisturbed old‐growth forests, but may play a very important (and scale/severity‐dependent) role in their response to disturbance. Understanding potential drivers and consequences of CSC in late‐successional forests will inform management focused on promoting complexity and old‐growth conditions, and illustrate potential impacts of such treatments on regional C dynamics.